IMPLEMENTASI PENDATAAN PENERIMA PROGRAM KELUARGA HARAPAN (STUDI KASUS DI DESA SUKA MAKMUR) - Sri Ulina; Bengkel Ginting; Malida Putri (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2022)
The Family Hope Program is one of the government programs that seeks to develop a social protection system for the poor in Indonesia. This program provides assistance in the form of cash to Very Poor Households (RTSM) provided that they must comply with the existing requirements. The initial data collection was carried out in determining the recipients of the Family Hope Program (PKH) assistance by following the data collection mechanism from the Central Statistics Agency (BPS), but after that the data collection was carried out by proposing DTKS where this proposal was carried out by the village or poor communities who volunteered to proposed to the Social Service which already has responsibility for the DTKS proposal. The purpose of this study was to see how the process of implementing the data collection for the Family Hope Program (PKH) in Suka Makmur Village. The research method is descriptive qualitative to get a clear picture of the implementation of data collection for the Family Hope Program (PKH). Data collection techniques with observational studies, interviews, and documentation. Based on the results of the study, it can be seen how the data collection process has been carried out and can also be seen how the data updating, verification and distribution of PKH funds to RTSM who receive the benefits can be seen. After conducting the research, it can be concluded that the process of implementing the data collection for the Family Hope Program has been going well even though there are still shortcomings in its implementation.